Magnetic properties of Ce-containing Pr/Nd-Fe-B sintered magnets by diffusing Nd-Dy-Al alloy - Liang, Liwei; Wang, Ruixiang; Chen, Dehai; Liu, Renhui; Ma, Pengfei; Wu, Tong; Wang, Haifeng (Frontiers in Materials, 2023)
In this study, 5% wt Ce-containing sintered Pr/Nd-Ce-Fe-B magnets were processed by grain boundary diffusion (GBD) with NdxDy90-xAl10 alloy (x = 0, 10, and 20 correspond to N0, N10, and N20, respectively). After the GBD process, the coercivity of magnets increased from 1,124.7 to 1,656.4, 1,673.9, and 1,584.8 kA/m, for N0, N10, and N20, respectively. Microstructure analysis revealed continuous RE-rich intergranular phases around matrix grains, which by weakening the magnetic coupling effect between ferromagnetic matrix grains, thus, leads to coercivity improvement. N10 had the same coercivity enhancement as N0, while the Dy utilization for N10 is lower than that for N0. The SEM results showed that the inclusion of Nd leads to the formation of a network of low-melting grain boundary phases, providing channels for subsequent Dy diffusion. A CeFe2 phase was found in the 5% wt Ce-containing magnet, which hindered diffusion due to its high melting point; in order to inhibit the negative impact of CeFe2 and reveal the diffusion mechanism in the Ce-containing magnet, DyH3, as a diffusion source, was applied to 5% wt-Ce-containing magnets simultaneously; after the GBD process, Nd10Dy90Al10 alloy, as a diffusion source, has better coercivity enhancement than DyH3, due to the deeper diffusion of the Dy element in the Nd10Dy90Al10 diffusion.